The small-scale urban reservoir fisheries of Lago Paranoá, Brasília, DF, Brazil - Walter,T. (2007)
In many cases in large urban centers, which have appropriate waterbodies, small-scale fisheries are the only source of cheap protein for the poor. In Lago Paranoá, located in Brasília, the capital city of Brazil, fishing was studied by conducting interviews with 53 fishers filling in logbooks from March, 1999 to March, 2000 in three fishing communities. The fishers come from the poorest towns around Brasília, known as satellite-towns. They have been living there on average for 21.7 years (s = 9.6 years), their families have 4.9 members (s = 3.6) on average and 44.2% do not have a basic education. However, such characteristics are similar to the socioeconomic indices of the metropolis where they live. In spite of being illegal between 1966 and 2000, fishing generated an average monthly income of U$ 239.00 (s = U$ 171.77). The Nile Tilapia Oreocrhromis niloticus is the main captured species (85% of a total number of landings in weight of 62.5 t.). Fishing is carried out in rowing boats, individually or in pairs. The fishing equipment used are gillnets and castnets. Gillnets were used actively, whereby the surface of the water is beaten with a stick to drive Tilapias towards nets as they have the ability to swim backwards. This fishing strategy was used in 64.7% of the fisheries, followed by castnets (31.1%) and by gillnets which were used less (4.2%). The fish is sold directly in the streets and fairs of the satellite-towns to middlemen or to bar owners. Three communities have different strategies in terms of fishing equipments, fishing spots and commercialization. Consequently, there are statistically significant differences in relation to the monthly income for each one of these communities.